Improving the Synthesis of Odd-Chain Fatty Acids in the Oleaginous Yeast Yarrowia lipolytica - Nour Tabaa Chalabi; Sally El Kantar; Camilla Pires De Souza; Anissa Khelfa; Jean-Marc Nicaud; Espérance Debs; Nicolas Louka; Mohamed Koubaa (Fermentation)
(1) Background: Odd-chain fatty acids (OCFAs) have garnered attention for their potential health benefits and unique roles in various biochemical pathways. Yarrowia lipolytica, a versatile yeast species, is increasingly studied for its capability to produce OCFAs under controlled genetic and environmental conditions. However, optimizing the synthesis of specific OCFAs, such as cis-9-heptadecenoic acid (C17:1), remains a challenge. (2) Methods: The gene coding for the Δ9 fatty acid desaturase, YlOLE1, and the gene coding the diacylglycerol O-acyltransferase 2, YlDGA2, were overexpressed in Y. lipolytica. With the engineered strain, the main goal was to fine-tune the production of OCFA-enriched lipids by optimizing the concentrations of sodium propionate and sodium acetate used as precursors for synthesizing odd- and even-chain fatty acids, respectively. (3) Results: In the strain overexpressing only YlDGA2, no significant changes in fatty acid composition or lipid content were observed compared to the control strain. However, in the strain overexpressing both genes, while no significant changes in lipid content were noted, a significant increase was observed in OCFA content. The optimal conditions for maximizing the cell density and the C17:1 content in lipids were found to be 2.23 g/L of sodium propionate and 17.48 g/L of sodium acetate. These conditions resulted in a cell density (optical density at 600 nm) of 19.5 ± 0.46 and a C17:1 content of 45.56% ± 1.29 in the culture medium after 168 h of fermentation. (4) Conclusions: By overexpressing the YlOLE1 gene and optimizing the concentrations of fatty acid precursors, it was possible to increase the content of OCFAs, mainly C17:1, in lipids synthesized by Y. lipolytica.